Effect of AL2O3, SIO2 and CNT nanoparticles blend fuels on diesel engine performances and emission characteristics - Anes, G. Mrwan; Ang, F. Chen; M. Akmal, Adzmi; M., Hafiz; K., Kamal; Mohd Fahmi, Othman; Abdul Adam, Abdullah (Universiti Malaysia Pahang, 2019)
This paper investigates the effect of three different types and concentration of nanoparticles on the performance and emission of diesel engine. The nanoparticles used in this research include aluminium oxide (Al2O3) nanoparticles, silicon oxide (SiO2) nanoparticles and carbon nanotubes (CNT) at 25, 50 and 100 ppm. The nanoparticles-diesel blend fuels were tested on YANMAR TF120M at engine speed of 1200 - 2400 rpm. CNT at 50 ppm (DC50) and CNT at 100 ppm (DC100) demonstrated highest BSFC improvement of 6.03% and 5.13%, respectively. Meanwhile, SiO2 at 100 ppm (DS100) demonstrated lower brake specific fuel consumption (BSFC) and brake thermal efficiency (BTE) of 7.97% and 7.49 % at 1200 rpm. Nonetheless, SiO2 at 25 ppm (DS25) had highest BTE of 8.77 % at 2400 rpm. All nanoparticles demonstrated CO reduction as its concentration increased. DA100 had maximum reduction CO of 41.2% at 2400 rpm. Furthermore, low amount of CNT of 25 ppm (DC25) reduced NOx average of 5.8 % across the tested engine speed. SiO2-diesel blend fuels had steady reduction of NOx at 7.64 % per ppm.